2014
DOI: 10.1007/s10578-014-0468-0
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Problems and Social Resource Factors Among Bullied Children in the Nordic Countries: A Population Based Cross-sectional Study

Abstract: This study estimated internalising and externalising mental health problems among bullied-, unclear if bullied- and not bullied children aged 4-16 in the Nordic countries, and identified resource factors to bullied children's mental health. Data comes from the cross-sectional NordChild survey 2011 and the Strength and Difficulties Questionnaire, including 6,214 children in the analyses. Mental health problems were most prevalent among children parent-reported as bullied (29.2-44.3 %), followed by children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 52 publications
1
17
0
1
Order By: Relevance
“…The results from this study support the findings in previous studies on mental health in bullied children as we identified a strong association between bullying and having mental health problems. We showed that bullying is associated with emotional symptoms, which is in line with the results reported in previous Nordic studies on depressive symptoms and bullying . Furthermore, a Nordic study showed that the more frequent children and adolescents were bullied, the higher the risk for poorer mental health.…”
Section: Discussionsupporting
confidence: 91%
“…The results from this study support the findings in previous studies on mental health in bullied children as we identified a strong association between bullying and having mental health problems. We showed that bullying is associated with emotional symptoms, which is in line with the results reported in previous Nordic studies on depressive symptoms and bullying . Furthermore, a Nordic study showed that the more frequent children and adolescents were bullied, the higher the risk for poorer mental health.…”
Section: Discussionsupporting
confidence: 91%
“…Bullying victimization is associated with mental health problems and bullied children continue to be at risk of poor social, health, and economic outcomes several decades after exposure (Bjereld, Daneback, Gunnarsdóttir, & Petzold, 2014;Kowalski, Giumetti, Schroeder, & Lattanner, 2014;Takizawa, Maughan, & Arseneault, 2014). In a study of time trends during 1994-2006 including 11-15-year-old school children in 21 European and North American countries, the largest decrease in occasional and chronic bullying victimization was measured in the Czech Republic (Molcho et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Experience of bullying victimization is associated with mental health problems (Bjereld et al . ), such as psychotic symptoms, self‐harm and violent behaviour, problems that can have long‐lasting effects (Arseneault et al . ; Takizawa et al .…”
Section: Introductionmentioning
confidence: 99%